Analysis of the state of socio-psychological adaptation, behavioral repertoire and social support as the main parameters of psychosocial functioning of patients with a history of combat traumatic brain injury depending on its severity and duration - Chernenko Інна; Markova Маріанна (Psychosomatic Medicine and General Practice, 2025)
УДК 616.89-07:616-036.82 Relevance. The conditions of martial law in the territory of Ukraine and its consequences affect the mental state of military personnel and the civilian population of the country, cause the emergence of a constant stressful state, the psychological consequences of which are very dangerous, lead to the deterioration of socio-psychological adaptation, mental health disorders: changes in the mental state due to constant anxiety, "expectation of the bad", suffering, acute reactions to stress, exacerbation of mental illnesses, alcohol and drug abuse, the development of depression and anxiety states. Aims. To analyze the state of socio-psychological adaptation, behavioral repertoire and social support as the main parameters of psychosocial functioning of patients with a history of combat traumatic brain injury depending on its severity and duration, to determine the directions of differentiation of therapeutic and rehabilitation approaches to this category of patients. Materials and methods. The features of the severity of psychopathological symptoms, including depressive, anxiety and post-traumatic, were studied in 350 patients with TBI of varying severity due to the action of a blast wave, taking into account the time elapsed since the injury. For this purpose, in each group according to the severity of TBI (mild (145 patients), moderate (125 people), severe (80 patients)), we identified three subgroups. Thus, the following groups of subjects were formed in the study: patients with mild TBI and the duration from the moment of injury to our examination from 6 to 12 months, numbering 35 patients; patients with mild TBI and the duration from the moment of injury from 1 to 3 years, numbering 60 patients; patients with mild TBI and the duration from the moment of injury from 4 to 7 years, numbering 50 patients; patients with moderate TBI and duration from the moment of injury from 6 to 12 months, in the number of 30 patients; patients with moderate TBI and duration from the moment of injury from 1 to 3 years, in the number of 45 patients; patients with moderate TBI and duration from the moment of injury from 4 to 7 years; patients with severe TBI and duration from the moment of injury from 6 to 12 months, in the number of 20 patients; patients with severe TBI and duration from the moment of injury from 1 to 3 years, in the number of 30 patients; patients with severe TBI and duration from the moment of injury from 4 to 7 years. The study of the features of psychosocial functioning was carried out using the methodology of the study of socio-psychological adaptation of K. Rogers - R. Diamond, the method of "Coping-test" by R. Lazarus and the Multidimensional Scale of Social Support. Results and discussion. The study of the features of the state of socio-psychological adaptation, taking into account the time since the TBI, allowed us to establish that the state of socio-psychological adaptation was characterized by a decrease in indicators characterizing adaptation and an increase in indicators characterizing maladaptive tendencies, with an increase in the duration of the disease. The study of the features of the coping repertoire in patients with different severity and the same duration of the disease revealed significant differences in the severity of different coping strategies in different groups. Analysis of the features of social support of patients with TBI of different severity, taking into account the duration of the disease, revealed a general tendency to reduce the level of social support with an increase in the duration of the disease. Conclusions. A clear trend towards worsening socio-psychological adaptation as the duration of the disease increases, regardless of the severity of TBI. In the coping repertoire of patients with TBI due to the action of the blast wave, a general pattern of increasing the expressiveness of non-constructive strategies and decreasing the expressiveness of constructive ones as the duration of the disease increases was revealed.